2021
DOI: 10.3389/fpubh.2021.810014
|View full text |Cite
|
Sign up to set email alerts
|

Users' Perception of Violence and Conflicts With Professionals in Primary Care Centers Before and During COVID-19. A Qualitative Study

Abstract: Background: Workplace violence is a social problem of special interest in both intervention and research. Among the sectors that most perceive this type of violence, health care professionals stand out. The most common type of violence for this professional group is the one perpetrated by the users or patients themselves. It has been reported that one out of every four acts of violence in the workplace occurs in the healthcare setting. Within the health sector, the Mental Health, Emergency and Primary Care ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…Both studies coincide in the inappropriate use of the system due to the user's lack of knowledge, deficit in consultation times that generates conflict, the professionals' lack of communication skills, the users' misuse of emergencies, depersonalized treatment and deficit in the management of psychosocial problems in PC. Likewise, both parties also seem to agree on some proposals identified in our study, such as the creation of support groups to decongest waiting lists, professional training and more information for the user ( 29 ). These studies show the need to create preventive interventions in PC centers focused on the sources of conflict and the proposals for improvement shared by both users and professionals.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Both studies coincide in the inappropriate use of the system due to the user's lack of knowledge, deficit in consultation times that generates conflict, the professionals' lack of communication skills, the users' misuse of emergencies, depersonalized treatment and deficit in the management of psychosocial problems in PC. Likewise, both parties also seem to agree on some proposals identified in our study, such as the creation of support groups to decongest waiting lists, professional training and more information for the user ( 29 ). These studies show the need to create preventive interventions in PC centers focused on the sources of conflict and the proposals for improvement shared by both users and professionals.…”
Section: Discussionsupporting
confidence: 60%
“…A recent study with PC users concluded that they positively value the changes in health care aimed at improving waiting times, comfort and the agility of procedures and bureaucracy. At the same time, they consider a source of conflict the lack of information on waiting times, the therapeutic process or the impersonal treatment by healthcare personnel ( 29 ). In short, the bibliography concludes that both education and training in the prevention and reduction of aggression are key aspects to address this problem.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, women and PHC personnel with fewer years of professional experience report greater exposure to non-physical violence (8). Furthermore, a recent qualitative study has explored the causes of conflicts in Primary Care centers (40). The aspects that seem to cause most con?icts between users and professionals from an organizational point of view are the uncertainty in waiting times, the need to adapt the telematic or telephone appointment to the different types of users, and the management of emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…The aspects that seem to cause most con?icts between users and professionals from an organizational point of view are the uncertainty in waiting times, the need to adapt the telematic or telephone appointment to the different types of users, and the management of emergencies. On the other hand, regarding the professionals, users pointed out that the medical staff is perceived as distant and sometimes does not provide enough information on the health status of users (40). Among the alternatives proposed to reduce the conflict are the incorporation of specific support sta?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation